Effects of hydroxycinnamic acids on the glycolysis pathway - Serina, J. (2021)
Glycolysis is a metabolic pathway vital to the production of energy and some organisms rely on it solely to meet their energy requirements. It is also a central pathway in the metabolism of carbohydrates and a source of therapeutic targets against diabetes and cancer. Caffeoylquinic acids (CQAs) have been extensively studied for their role in the treatment and prevention of diabetes (and cancer) but their mechanisms of action remain mostly unknown. As such, molecular docking was used to find possible targets of CQAs in the glycolysis pathway. The molecular docking assays showed that CQAs were docked preferably to the Rossman fold (nicotinamide adenine dinucleotide — NAD(H) binding site) of oxidoreductases, that use NAD(H) as a cofactor, than to any other site. In-vitro assays were then performed using two NAD(H) dependent oxidoreductases from glycolysis (alcohol dehydrogenase and L-lactate dehydrogenase) in order confirm if CQAs would compete with the cofactor to inhibit the reaction. The results from these assays indicate that CQAs can act as both inhibitors and activators of NAD(H) dependent oxidoreductases of the glycolysis pathway.